PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI SISWA - Rosdayana Putri Azhari; Tutut Nurita (PENSA: E-JURNAL PENDIDIKAN SAINS, 2021)
This study was conducted to determine the improvement of students' written communication skills using discovery learning learning models on global warming materials. The type of research used is experimental. The subject of the study was smpn 58 Surabaya grade VII-A students who numbered 30. The research instruments are written communication skills test sheets totaling five description questions, observation sheets of discovery learning implementation, and student response questionnaires. Data collection techniques are carried out by test, observation, and questionnaire methods. The research data was analyzed through the results of the implementation of the discovery learning model, written communication skills test sheet, and student response questionnaire data. The results of the implementation of learning at the first meeting and the second meeting obtained a percentage between 93.75%-100% with an excellent category, N-Gain score on the indicator describes the object scored 0.90 with a high category, the indicator applies the concept of knowledge appropriately and according to the material and clarifies with supporting sentences obtain a score of 0.54 with a moderate category, indicators make tables and graphs score 0.81 with a high category, indicators analyze and process observation data through tables and graphs get a score of 0.82 with a high category, and indicators write the results of activities of an event obtained a score of 0.98 with a high category, N-Gain scores for all indicators of written communication skills were obtained 0.81 with a high category, and in the questionnaire the student response obtained an overall average of 86.67% aspects with excellent categories. The conclusion of this study is that learning with discovery learning model can improve students' written communication skills based on the average N-Gain score of all indicators of written communication skills.